Sugar Beet Agronomic Performance Evolution in NW Spain in Future Scenarios of Climate Change - Luis Fernando Sánchez-Sastre; Nuno M. S. Alte da Veiga; Norlan Miguel Ruiz-Potosme; Salvador Hernández-Navarro; José Luis Marcos-Robles; Jesús Martín-Gil; Pablo Martín-Ramos (Agronomy, 2020)
Changes in environmental conditions resulting from Climate Change are expected to have a major impact on crops. In order to foresee adaptation measures and to minimize yield decline, it is necessary to estimate the effect of those changes on the evapotranspiration and on the associated irrigation needs of crops. In the study presented herein, future conditions extracted from RCP4.5 scenario of IPCC, particularized for Castilla-y-León (Spain), were used as inputs for FAO crop simulation model (AquaCrop) to estimate sugar beet agronomic performance in the medium-term (2050 and 2070). A regional analysis of future trends in terms of yield, biomass and CO2 sequestration was carried out. An annual ET0 increase of up to 200 mm was estimated in 2050 and 2070 scenarios, with ETc increases of up to 40 mm/month. At current irrigation levels, temperature rise would be accompanied by a 9% decrease in yield and a ca. 6% decrease in assimilated CO2 in the 2050 and 2070 scenarios. However, it is also shown that the implementation of adequate adaptation measures, in combination with a more efficient irrigation management, may result in up to 17% higher yields and in the storage of between 9% and 13% higher amounts of CO2.